Associations between biological maturity level, match locomotion, and physical capacities in youth male soccer players - Gundersen, H.; Riiser, A.; Algroy, E.; Vestbøstad, E.; Saeterbakken, A. H.; Clemm, H. H.; Grendstad, H.; Hafstad, A.; Kristoffersen, M.; Rygh, C. B. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Introduction Biological maturity level has shown to affect sport performance in youths. However, most previous studies have used noninvasive methods to estimate maturity level. Thus, the main aim of the present study was to investigate the association between skeletal age (SA) as a measure of biological maturation level, match locomotion, and physical capacity in male youth soccer players.